STATISTICAL INVESTIGATION OF THE EFFECTS OF MAIN MACROECONOMIC VARIABLES ON STOCK MARKET PERFORMANCE IN NIGERIA USING ARDL MODEL - ALEMHO, J. E. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
The effect of the main macroeconomic variables on the stock market performance has been of great concern recently. This has necessitated divers conference of researchers and government agencies reforms geared towards improving the stock market performance and a stable growth of the Nigeria economy. The study seeks to examine the effect of Inflation Rate, Interest Rate and Exchange Rate on the performance of the stock market using ARDL Model on data obtained from the Central Bank of Nigeria (CBN) statistical bulletin for the period of 1985-2018. The study employed the Augmented Dickey Fuller test to test for stationarity among the variables, Johensen cointegration technique is use to determine the order of cointegration. Granger causality test was used to check for causal relationship among the variables and then the Autoregressive Distribution Lag (ARDL) Model to check for a short-run or long-run relationship among the variables. The results indicate that all the variables are non-stationary at levels, but became stationary after first differencing. The three macroeconomic variables were also cointegrated. There is a causality runs among these variables. The ARDL Model suggested a short and long-run relationship between stock market performance and the three macroeconomic variables. The CUSUM and CUSUMSQ plots (serving as a stability test) are within the critical bounds meaning that the model is stable. The selected macroeconomic variables were found to have a significant effect on the Nigeria stock market performance. The implication of the findings is that a decrease in inflation rate and other variables will improve the performance of the stock market in Nigeria both in short term and long-term. The study therefore recommends among others that the investors should pay more attention to the macroeconomic variables and not only the stock market performance.